SOCIO ECONOMIC STUDY HOUSEWIFE OIL PALM PLANTATION WORKERS PAUH TERENJA VILLAGE XIV KOTO DISTRICT MUKOMUKO REGION - NOVITA, NOVA MIA; Erita, Yeni; Prari Keslan, Rozana Eka (Pendidikan Geografi, 2014)
ABSTRACTÂ Â This study aimed to obtain, analyze and discuss about Socio-Economic Housewife Oil Palm Plantation Workers Pauh Terenja village XIV Koto District Mukomuko region views of : 1) education, (2) skills and (3) incomeThis research is classified as descriptive. Population was a homemaker palm plantation workers in Pauh Terenja village XIV Koto District Mukomuko region and double roles in working in the oil palm plantation as many as 50 people. Sample of respondents was taken by total sampling as many of the 50 people. Collecting data using guided inquiry, statistical analysis used was descriptive using percentage formula . The results showed as follows ; 1 ) the level of education housewives oil palm plantation workers Pauh Terenja village XIV Koto District Mukomuko region, formal education is generally completed primary school and no informal education, (2) skills housewife working in Oil Palm Plantation Pauh Terenja village XIV Koto District Mukomuko region, generally have the appropriate skills to work and are satisfied with the salary earned and (3) income housewives oil palm plantation workers Pauh Terenja village XIV Koto District Mukomuko region, generally income of Rp 500.000 - Rp 800.000/month and labor expenses housewife Palm plantation Pauh Terenja village XIV Koto District Mukomuko region generally Rp 268.000 to Rp 374.000/monthÂ